Computational collective intelligence. 10th International Conference, ICCCI 2018, Bristol, UK, September 5-7, 2018, Proceedings /: 10th International Conference, ICCCI 2018, Bristol, UK, September 5-7, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available